1998
DOI: 10.1093/jmedent/35.4.551
|View full text |Cite
|
Sign up to set email alerts
|

A New Ecology for Scrub Typhus Associated with a Focus of Antibiotic Resistance in Rice Farmers in Thailand

Abstract: Following the documentation of chloramphenicol-resistant and doxycycline-resistant strains of Orientia tsutsugamushi (Hyashi) in northern Thailand, we conducted ecological and epidemiological studies near the houses of patients hospitalized with antibiotic-resistant infections. New associations between chiggers, rodents, and O. tsutsugamushi in active rice agriculture areas, an ecological habitat not described previously, are reported. Rattus rattus (L.) was the most common species (representing 85.8% of the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 0 publications
1
32
1
Order By: Relevance
“…Historically, high O. tsutsugamushi infection rates have been found in chiggers, rodents, and humans from this area. 5,7,20,21 In this study, infected mammals were found in only four (Chiangrai, Bangkok, Nonthaburi, and Sukothai) of eight provinces; however, 99.6% (563 of 565) of infected mammals were found in Chiangrai Province, with only a single infected animal found in Bangkok, Nonthaburi, and Sukothai Provinces. Certain species of animals with low O. tsutsugamushi infection rates were rarely found in Chiangrai Province.…”
Section: Discussioncontrasting
confidence: 66%
See 4 more Smart Citations
“…Historically, high O. tsutsugamushi infection rates have been found in chiggers, rodents, and humans from this area. 5,7,20,21 In this study, infected mammals were found in only four (Chiangrai, Bangkok, Nonthaburi, and Sukothai) of eight provinces; however, 99.6% (563 of 565) of infected mammals were found in Chiangrai Province, with only a single infected animal found in Bangkok, Nonthaburi, and Sukothai Provinces. Certain species of animals with low O. tsutsugamushi infection rates were rarely found in Chiangrai Province.…”
Section: Discussioncontrasting
confidence: 66%
“…All procedures involving animals were conducted under animal use protocols approved by the Armed Forces Research Institute of Medical Sciences Institutional Animal Care and Use Committee. Small mammals were routinely collected during studies on the epidemiology of scrub typhus in Chiangrai, 7,20,21 Nonthaburi, 18 and Phitsanulok 21 Provinces of Thailand. Collections in additional provinces were made on an irregular basis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations